The Effect of Generating Interaction Between Schemata and Text (GIST) Strategy on Reading Narrative Text of SMK YPIS MAJU Binjai - Ayu Indari; Don Atmaja (English Teaching and Linguistics Journal (ETLiJ), 2021)
The objective of this research is to find out the effect of Generating Interaction between Schemata and Text (GIST) Strategy on reading the narrative text of the 2019/2020 tenth years of SMK YPIS Maju Binjai. This research conducted in SMK YPIS Maju Binjai, which is located on Jl. T. Amir Hamzah village Jati Utomo District of North Binjai Binjai.  In this study the sample is divided into 2 groups namely the control class and the experimental class. Each class consists of 32 students. The control class is a class that does not apply the GIST Strategy while the experimental class is a class that uses the GIST Strategy. In this research method is the type of experimental research which is one type of research which aims to provide an overview of the influence of variables x and y variables. The average value of the pretest and posttest the student's ability to control class was 64.4 and 67,2  with standard deviation value of 9.6 and 9,3. The average value of the pre-test and post-test the student's ability experimental class was 70,6 and 78,6 with a standard deviation of 6,9 and 7,5. Based on data normality testing it is known that the overall data both control class and experimental class data are normally distributed data. While the homogeneity of data testing is known that the overall data is homogeneous type. With the price of t = 64,3, r criticism known price at the level of 5% gained 3,65 then 64,3 > 3,65, then the hypothesis of a significant means of experiments conducted have an influence on the experimental group. So that the proposed hypothesis that there is significantly effect of Generating Interaction Between Schemata and Text (GIST) Strategy on reading the narrative text of the 20 19/2020 tenth years of SMK YPIS Maju Binjai”.